Effect of milling parameters and magnesium doping on structural and optical properties of nano zinc oxide synthesized by mechanochemical processing / Nursyahadah Mohd Zor - Mohd Zor, Nursyahadah (2013)
Nanoparticles of undoped and Magnesium doped Zinc Oxide were prepared using mechanochemical synthesis. Zinc Chloride, Sodium Carbonate and Sodium Chloride were milled together in ball mill with different period of milling time and molarity of Sodium Chloride as diluents agent added to analyze the effect of different milling parameters on structural and optical properties of Zinc Oxide obtained. After milling, the samples were subjected to different heat treatment process and analyzed using XRay Diffraction spectrometer to check the progress of reaction and find the crystallite sizes of nanopowders. UV-Vis spectroscopy was employed to get the value of energy gap for the samples while Field Emission Scanning Electron Microscope are used to observe the microstructure of samples. From the result, the best optimum time to synthesis nanoparticles Zinc Oxide with lowest particle size is 5 hours and the optimum amount of diluent (PCA) to use in this technique is 6 moles. Other than that, the increasing of heat treatment temperatures was found to increase the crystallite sizes of nanoparticles obtained. ZnO nanoparticles displayed significant recovery of defects that were introduced during milling process as evidenced by XRD analysis. Magnesium doping is seen to influence the crystallite size by arresting the crystal growth during milling and heat treatment. From the synthesized ZnO nanoparticles, it can be seen that crystallite size of the nanoparticles displayed an inversely proportional relationship with energy gap value after prepared with different milling conditions and ratio of Magnesium doping. The increasing of energy gap with the decreasing crystallite size is attributed to the quantum confinement effects.